Applications of information navigation method in wireless sensor networks - Wei WEI; Liang ZHANG; De-ke GUO; Pei-yi SHEN (Tongxin xuebao)
For adapting to a novel architecture of WSNs,which supports information query and navigation systems through construction of the virtual potential field.Under the premise of diffusion equation and poisson-based formula,a novel method was proposed which can accomplish the navigation more conveniently and more efficiently.In order to guarantee the accuracy of navigation,the relative knowledge of information transmission and the partial differential process(diffusion equation)in electric potential field was utilized,meanwhile gradient descent method was also applied in the process of application.A complete mathematical derivation was used.Tiny-OS simulations show the method can efficiently overcome the original WSNs weakness that network configuration abilities of information navigation are not good enough.Simultaneously,during the process of explore the navigation computation,structures of diffusion equation are more flexible and adaptability.